Black art: A discussion - Araeen, Rasheed; Chambers, Eddie (Third Text, 1988)
Disponible en ligne: https://www.tandfonline.com/doi/abs/10.1080/09528828808576204
Keywords: antiracisme; approches et analyses; arts; asie; cours; discipline; europe; har4610; histoire de l'art; premier cycle; royaume-uni; régions géographiques

Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Section: 239 p. : ill. ; 24 cm
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques